I need help with this please!Solve | 8x | ≥ 32
Select the appropriate response
A) x≥5
B) x≥7
C) x≥4
D) x≥9

Answers

Answer 1
Answer:

Answer:

C) x≥4  and  x   ≤ -4

Step-by-step explanation:

| 8x | ≥ 32

To remove the absolute values, we get two equations, one positive and one negative

8x ≥ 32         and     8x   ≤ -32

Divide each side by 8

8x/8 ≥ 32/8         and     8x/8   ≤ -32/8

x ≥ 4        and           x   ≤ -4


Related Questions

A ball is dropped from a height of 12 feet and returns to a height that is one-half of the height from which it fell. How far will the ball have traveled when it hits the ground for the fourth time?A. 12 feet B. 24 feet C. 3 feet D. 33 feet **my answer: D. 33 feet not too sure tho.. is that right?
Solve for x: x-1/4=1/2 help please
Simply the equation and show your work
If a plant manufacturing carpet backing has a cylindrical tank that is 3 meters high and is 6 meters in diameter, what is the volume of the tank? Assume 3.14 for pi.A)28.3 m^3 B)37.7 m^3 C)56.5 m^3 D)84.8 m^3
The reciprocal of a nonzero real number of the form a/b is:Select one: O a. b/a Ob. a + b Oc a-b O d. undefined

car travels the distance between Delhi and Karnal in 3 hours. If the distance between the two towns is 120km. What is the average speed of the car?

Answers

Answer:

v = 40 km/h

Step-by-step explanation:

In the picture below

48.6 is what percentage %? of 24.3 simplify

Answers

48.6 is 200% of 24.3

Divide:

48.6 / 24.3 = 2

Change to percentage:

2 × 100 = 200
It has doubled so 24.3 is 100%. 100%x2=200%. It is 200% of it.

If f(x) = x3 – 2x2, which expression is equivalent to f(i)? A) –2 + i
b) –2 – i
c) 2 + i
d) 2 – i

Answers

Answer

d) 2 – i


Explanation

f(x) = x³ – 2x²

When x = i, we proceed as follows.

Note: i =

          i² =(√-1)(√-1) =  -1

          i³ = (√-1)(√-1)(√-1) = -1(√-1) = -1i = -i

f(x) = x³ – 2x²

f(i) = i³ – 2i²

     = -i – 2(-1)

     = -i + 2

      = 2 – i


Answer:

f(i)=2-i

d is the correct option.

Step-by-step explanation:

The given function is f(x)=x^3-2x^2

Substitute x = i, to find f(i)

f(i)=i^3-2(i)^2

We can rewrite this as

f(i)=i^2\cdot i-2(i)^2

Now, we know thati^2=-1. Thus, we have

f(i)=(-1)\cdot i-2(-1)

On simplifying, we get

f(i)=-i+2\n\nf(i)=2-i

d is the correct option.

Refer to the triangle below. If a = 3 and b = 6
a. Find the exact length of c in un-simplified radical form
b. Find the exact length of c in simplified radical form
c. Find c to the nearest hundredth.

Answers

By the Pythagorean theorem:

с = √(3² + 6²) 
   = √(9 + 36)
   = √45     ← un-simplified radical form
   = 3
√5     ← simplified radical form 
   
≈ 6.71    ← to the nearest hundredth

How many times can 8 go into 66

Answers

8 can go 8.25 or 8 1/4 times in 66. This is done by using a basic mathematical operation which is division. 66 is divided by 8 which will give us the result of 88.25 or in fraction form it would be 8 1/4.

A 8 can go into 66 eight times, with a remainder of 2.

To calculate how many times 8 can go into 66, we need to perform long division.

Step 1: Set up the long division:

     8 | 66

Step 2: Determine how many times 8 can go into the first digit of 66 (which is 6). It goes 8 times (8 x 8 = 64). Write 8 above the division bar.

     8 | 66

        8

Step 3: Subtract 64 from 66 to get the remainder. Bring down the next digit (which is 6).

     8 | 66

        8

       ---

         26

Step 4: Determine how many times 8 can go into 26. It goes 3 times (8 x 3 = 24). Write 3 above the division bar.

     8 | 66

        8

       ---

         26

        24

Step 5: Subtract 24 from 26 to get the remainder. There is no more digit to bring down, so the division is complete.

     8 | 66

        8

       ---

         26

        24

       ---

          2

The final result is 8 times with a remainder of 2. Therefore, 8 can go into 66 eight times, with a remainder of 2.

To know more about remainder:

brainly.com/question/29019179


#SPJ6

What is the y-value of the solution to the system of equations? 3x + 5y = 1 7x + 4y = −13

Answers

3x + 5y = 1 . . . . . . . . (1)
7x + 4y = -13 . . . . . . .(2)
(1) x 7: 21x + 35y = 7 . . (3)
(2) x 3: 21x + 12y = -39 .(4)
(3) - (4) = 23y = 46
y = 46/23 = 2

Answer:

2

Step-by-step explanation: